2019
DOI: 10.1186/s13063-019-3633-8
|View full text |Cite
|
Sign up to set email alerts
|

Hope and despair: a qualitative exploration of the experiences and impact of trial processes in a rehabilitation trial

Abstract: Background Unanticipated responses by research participants can influence randomised controlled trials (RCTs) in multiple ways, many of which are poorly understood. This study used qualitative interviews as part of an embedded process evaluation to explore the impact participants may have on the study, but also unintended impacts the study may have on them. Aim The aim of the study was to explore participants’ experiences and the impact of trial involvement in a pilot R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The expressed hope and expectations of personal bene t for recovery are consistent with the main reasons for participation stated by patients in our trial. Assumptions of therapeutic bene t from participation in (stroke rehabilitation) research has also been found and discussed in other studies (23,24).…”
Section: Bene Ts and Concerns Related To Rtms Treatmentmentioning
confidence: 84%
See 1 more Smart Citation
“…The expressed hope and expectations of personal bene t for recovery are consistent with the main reasons for participation stated by patients in our trial. Assumptions of therapeutic bene t from participation in (stroke rehabilitation) research has also been found and discussed in other studies (23,24).…”
Section: Bene Ts and Concerns Related To Rtms Treatmentmentioning
confidence: 84%
“…Some patients shared concerns about allocation to the control group, which could limit their chance of additional improvement. Several studies have explored the psychological burden for patients participating in an RCT, who were informed by the result of randomization, and acknowledged the discomfort of being randomized, and anxiousness or embarrassment to receive placebo (23,43). However, in our study the patients were unaware of group allocation.…”
Section: Bene Ts and Concerns Related To Rtms Treatmentmentioning
confidence: 99%
“…The expressed hope and expectations of personal bene t for recovery are consistent with the main reasons for participation stated by patients in our trial. Assumptions of therapeutic bene t from participation in (stroke rehabilitation) research has also been found and discussed in other studies [21,22].…”
Section: Bene Ts and Concerns Related To Rtms Treatmentmentioning
confidence: 84%
“…Some patients shared concerns about allocation to the control group, which could limit their chance of additional improvement. Several studies have explored the psychological burden for patients participating in an RCT, who were informed by the result of randomization, and acknowledged the discomfort of being randomized, and anxiousness or embarrassment to receive placebo [21,40].…”
Section: Bene Ts and Concerns Related To Participation In An Rctmentioning
confidence: 99%
“…Some patients shared concerns about allocation to the control group, which could limit their chance of additional improvement. Several studies have explored the psychological burden for patients participating in an RCT, who were informed by the result of randomization, and acknowledged the discomfort of being randomized, and anxiousness or embarrassment to receive placebo [27,47]. However, in our study the patients were unaware of group allocation.…”
Section: Benefits and Concerns Related To Participation In An Rctmentioning
confidence: 99%